Risiko Penurunan Kondisi Kesehatan Mental pada Remaja Pengguna Media Sosial yang Melakukan Self-diagnose - Affandi, Amanda Audrey (Fakultas Psikologi Universitas Sanata Dharma, 2024)
The existence of information technology, especially internet bring increase awareness about mental health. On the other hand, the abundance of this information on internet and lack of understanding from adolescence about dynamics of mental health disorders bring negative impact of self diagnose. This research purposes to reveal the picture of self diagnose with adolescence mental health which social media user, the psychological impact, also what role social media do for the phenomenon. Methods of this research are qualitative methods with phenomenology design. Data collected with semi- structured interview with 4 participants (16-17 years old, 50% women) that already did a self diagnose and active on social media. Analysis technique use in this research is thematic research. The results are that all participants are curious about their mental health condition and sense of their mental illness symptoms, so that they search for information about their mental health from social media on the internet. This self-diagnosed behavior appears when they believe what happened to themselves are the same with mental health disorders. This what bring impact on their psychological such as worried, fear, even wakeful. Self diagnose without validation from professional mental health worker could trigger cognitive process to misunderstanding and false belief about the condition of their mental health and bring up a negative psychological impact.